Recomendação de algoritmos de aprendizado de máquina para predição de falhas de software por meio de meta-aprendizado - Alves, Luciano (2016)
Software fault prediction is a significant part of software quality assurance and it is commonly used to detect faulty software modules based on software measurement data. Several machine learning based approaches have been proposed for generating predictive models from collected data, although none has become standard given the specificities of each software project. Hence, we believe that recommending the best algorithm for each project is much more important and useful than developing a single algorithm for being used in any project. For achieving that goal, we propose in this dissertation a novel framework for recommending machine learning algorithms that is capable of automatically identifying the most suitable algorithm according to the software project that is being considered. Our solution, namely FMA-PFS, makes use of the metalearning paradigm in order to learn the best learner for a particular project. Results show that the FMA-PFS framework provides both the best single algorithm recommendation and also the best ranking recommendation for the software fault prediction problem.